ANALYSIS OF THE STATE OF INDUSTRIAL TRAUMATISM BY REGIONS OF UKRAINE - Berezovskyi, A. P.; Trus, O. M.; Prokopenko, E. V. (Scientific Progress & Innovations, 2021)
Despite the introduction of modern and safer technologies, the issue of industrial injuries is still relevant today. The purpose of the presented review was to provide an analysis of the state of occupatrional injuries, including lethal in the regions of Ukraine, and determine the main causes of their occurrence as well as to conduct a comparative analysis of industrial traumatism during 2016–2020. The analysis of the state of accidents at enterprises in the regions of Ukraine was carried out according to the official data of the executive directorate bodies of the Social Insurance Fund of Ukraine. It has been established that the indicators of general injuries tend to decrease. The level of fatal injuries remains high. In 2017, compared to 2016, the number of accident victims increased by 4.2 % and the number of fatally injured persons decreased by 8.8 %. During 2017–2019 there was a decrease in the number of accidents at workplace as well as an increase in the number of fatally injured persons. As a result of the coronavirus pandemic (COVID–19) in 2020 there was a sharp increase in the number of victims of accidents at work – 6,646 persons (including fatally injured – 393), which is 51.3 % more than in 2019, and the number of fatally injured persons decreased by 4.1 %. Of these, 3,054 (including fatally injured – 66) were the victims of acute occupational diseases with the diagnosis of COVID–19 which makes 46 % of the total number of victims. 3,592 persons (327 of whom were fatally injured), victims of accidents at work were registered in 2020, excluding COVID–19 acute occupational disease. Compared to 2019, the number of accidents excluding COVID–19 decreased by 18.3 % and the number of fatally injured persons decreased by 20.2 %. In 2016–2020, the most injurious regions of Ukraine, including fatal accidents were: the city of Kyiv, Dnipropetrovsk, Donetsk, Lviv, Zaporizhzhia, Kyiv and Kharkiv regions. Among the main causes of accidents, the first place was occupied by organizational (62.9 %), the second – psychophysiological (19.5 %), the third – technical (11.0 %), and the fourth place – other reasons (6.0 %). Also 0.6 % of workers were injured due to anthropogenic, natural, environmental and social reasons.